2018
DOI: 10.1039/c8sc00256h
|View full text |Cite
|
Sign up to set email alerts
|

A thioether-directed palladium-cleavable linker for targeted bioorthogonal drug decaging

Abstract: We describe the development of a bifunctional linker that simultaneously allows site-specific protein modification and palladium-mediated bioorthogonal decaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 31 publications
3
60
0
Order By: Relevance
“… 38 As a result, much of the research pertaining to 1 and their anthracycline analogues focuses on suppressing the cardiotoxic effect of this class of cytotoxic drugs. A variety of prodrug strategies are currently under investigation to improve tumour targetability 39 43 and have shown that blockade of the primary amino group of the daunosamine moiety of 1 significantly reduces the bioactivity of the resulting derivative. Based on this evidence, the masking of the NH 2 group as a carbamate group was investigated to develop novel biochemically-stable, Pd-sensitive prodrugs of 1 ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 38 As a result, much of the research pertaining to 1 and their anthracycline analogues focuses on suppressing the cardiotoxic effect of this class of cytotoxic drugs. A variety of prodrug strategies are currently under investigation to improve tumour targetability 39 43 and have shown that blockade of the primary amino group of the daunosamine moiety of 1 significantly reduces the bioactivity of the resulting derivative. Based on this evidence, the masking of the NH 2 group as a carbamate group was investigated to develop novel biochemically-stable, Pd-sensitive prodrugs of 1 ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pd, Ru, Au) have been shuttled into living cells, tissues and animals in pursuit of tools capable of catalysing first-in-life reactions. From organometallic complexes, [1][2][3][4][5][6][7][8][9][10][11][12][13] artificial metalloenzymes [14][15][16] and metal-loaded nanocarriers [17][18][19][20][21][22][23][24] to larger-than-cells implantable devices, [25][26][27][28][29][30][31] a selected number of agents have demonstrated catalytic activity and maintained their functional compatibility with the biological milieu. Although the development of effective intracellular catalysts based on abiotic metals remains challenging, various examples reported in the literature have tested the feasibility of this concept.…”
Section: Introductionmentioning
confidence: 99%
“…The use of transition metals to locally activate prodrugs is ar elated strategy. [95] Studies done with variousm etal constructs have established the concept in vitro, [22,25,27,93,96] in zebrafish through the uncaging of af luorophore, [25b, 27] and recently in mice. [20a, 26] Dissociative bioorthogonal reactions can also be combined with antibody-drug conjugates (Scheme13B).…”
Section: Using Dissociative Chemistry For Drug Deliverymentioning
confidence: 99%